Issues of improving the legislation of the republic of kazakhstan to ensure the legality of management acts - Kubeyev, Y.K.; Musilimova, K.; Ilyassova, G.; Bozhkarauly, A.; Akhmetova, N.; Rustembekova, D. (My University, 2016)
The purpose of this article is theoretical and legal analysis of the scientific literature, and legislation of the Republic of Kazakhstan on the topical problems of ensuring the legality of management acts, making suggestions and recommendations on improvement of legislation and law enforcement practice in the sphere of public administration. The urgency of this problem is determined by the need to further improvement of the organizational and legal mechanism of insuring the legality in public administration, protection of rights and legal interests of citizens. Studying this problem in the scientific researches of Kazakhstani and foreign authors, the Republic of Kazakhstan legislations show that the issues of ensuring the legality of management acts in the Republic of Kazakhstan are paid much attention. The main results of the study are as follows: - in management practice all illegal acts, even those that contain obvious and gross defects are voidable, i.e.it is necessary to use measures of state and legal effects provided by the legislation to stop their actions; - in the Law of the Republic of Kazakhstan «On normative legal acts», one should establish that the state registration shall be subject to all legal acts, except for those by which the internal relations between the executive authorities and their structural divisions are governed; - it is necessary to establish the science-based concept of administrative justice model, the adoption of the Administrative Procedure Code in the Republic of Kazakhstan; - in the Constitutional Law of the Republic of Kazakhstan «On the Constitutional Council of the Republic of Kazakhstan» it is necessary to set a standard on the application of courts to the Constitutional Council in the procedure established by Article 78 of the Constitution, the effect of the contested act in cases of urgency should be suspended for a period of consideration its Constitutional Council»; it is expedient to empower the appeal of the Prosecutor General of the Republic of Kazakhstan to the Constitutional Council.
Keywords: the Republic of Kazakhstan; legality; legal acts of management; normative legal acts; administrative justice